PRESERVATION OF FISH BY FREEZING AND GLAZING 1. BACTERIOLOGY OF FRESH, FROZEN AND GLAZED FISH - JADHAV, M G; MAGAR, N G (Fishery Technology, 2025)
Microbiological investigation of fresh and frozen fishes suchas pomfret, surmai and mackerel was carried out under variousconditions of preservation. Glazing, block-freezing and preservationin gunny bag were effected. Determination of bacterial load andisolation, identification and classification of the resistant bacteriawere niade. Spore-formers of Subtilis mesentericus group werefound to be resistant to freezing as well as glazing by ascorbic acid,citric acid and sodium nitrite except a mixture of sodium chlorideand glucose. Bacterial load was reduced to a good extent andmaintained low till the end of frozen storage period.